(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In the conditions of today’s globalization, the role and participation of higher education institutions in maintaining the purity of our national language, increasing its vocabulary, increasing the speech culture of the population, ensuring the active integration of the state language into modern information technologies and communications, and increasing the position and prestige of the state language at the international level should be clearly demonstrated.